EVALUATING THE IMPACT OF ACCOUNTING DISCLOSURE OF SOCIAL RESPONSIBILITY IN ENHANCING THE TRANSPARENCY OF THE SUSTAINABLE REPORT - Murtada Taha Eesa; Sadeq Hadi Muhi; Jasim IdanBarrak (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The research aims to identify the extent of the contribution of accounting disclosure on social responsibility in enhancing the transparency of information in sustainable reports. To achieve this goal, social responsibility was defined and the role of its disclosure in enhancing the transparency of sustainable reports was evaluated